La définition progressive d’une politique européenne de sécurité - Cristian Iordan (Romanian Journal of European Affairs)
This article looks upon the evolution of the idea of a European security policy, in a historical approach, based on the major challenges, statistics on defence, and some recent developments in the matter of defence budgets, but also at the European Union international identity as civilian power, normative power, or soft power.